1956
DOI: 10.1246/bcsj.29.311
|View full text |Cite
|
Sign up to set email alerts
|

Absorption Spectra of Co(III) Complexes. II. Redetermination of the Spectrochemical Series

Abstract: The visible and ultra-violet absorption spectra of many cobaltic ammine, oxalato, carbonato and amino-acido complexes have been determined in solution. The spectrochemical series for the ligands of Co(III) complexes has been redetermined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
37
0

Year Published

1963
1963
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(41 citation statements)
references
References 24 publications
4
37
0
Order By: Relevance
“…1, left) is symmetrical and sharp and is a little more intense than the T2, band. The same features have been observed for cis and trans amino acid complexes such as [Co(gly),], [Co(DL-ala),], and [Co(L-leu),] (8,9).' Here the isomers with noticeable splittings in the TI, bands were assigned as the trans (or meridional) isomers and those with symmetrical sharp TI, bands as the cis(or facial) isomers.…”
Section: Electronic Spectrasupporting
confidence: 62%
“…1, left) is symmetrical and sharp and is a little more intense than the T2, band. The same features have been observed for cis and trans amino acid complexes such as [Co(gly),], [Co(DL-ala),], and [Co(L-leu),] (8,9).' Here the isomers with noticeable splittings in the TI, bands were assigned as the trans (or meridional) isomers and those with symmetrical sharp TI, bands as the cis(or facial) isomers.…”
Section: Electronic Spectrasupporting
confidence: 62%
“…For structures built up from H 2 O and CH 3 CN, inversion symmetry was recovered. Optimized complexes composed of ox 2À , NH 3 , and en did not show any symmetry element. Table 1 reports for the different ligands the spin-philicity w þ S;total , obtained through Equation (13), the projected w þ S;Metal on the metal center, cited Jørgensen's f values [4] and d Co Shimura parameters.…”
Section: Spin-philicity Concept Applied To the Spectrochemical Seriesmentioning
confidence: 90%
“…
The spectrochemical series represents the order of hypsochromic effect on the first or second absorption band of metallic complexes. Before Tsuchida's observations of this series, [1][2][3] Werner already discovered a regularity in the hypsochromic influence with the first neighbor atom of the ligand. [4] In the past, this series was identified from cobaltA C H T U N G T R E N N U N G (III) complexes on the basis of pure empiricism.
…”
mentioning
confidence: 99%
“…The numerical values of the absorption maxima are summarized in Table 2, together with those of related compounds. [5][6][7][8][9][10] It is found that the first bands of the complex I, II, and III have the only one peak located at sites of higher energy than that of the fac-(N3O3) type chromium(III) complexes, [Cr(L)3](L=anions On the other hand, the four cobalt(III) comtively. Since the interpretations of the absorption peaks of cobalt(III) complexes are thought to hold also for the discussions of those of chromium(III) Fig.…”
Section: Methodsmentioning
confidence: 99%